2023
DOI: 10.3390/antibiotics12091440
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infections in Children

Julie Nguyen,
Kallirroi Kotilea,
Patrick Bontems
et al.

Abstract: In the context of epidemiology, host response, disease presentation, diagnosis, and treatment management, the manifestation of Helicobacter pylori (H. pylori) infection diverges between children and adults. H. pylori infection stands out as one of the most prevalent bacterial infections globally, and its prevalence in both children and adults is decreasing in many developing countries but some still struggle with a high prevalence of pediatric H. pylori infection and its consequences. The majority of infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Household transmission, including oral-to-oral, fecal-oral, and gastrointestinal routes, is the primary mode. Approximately 90% of H. pylori infection cases are asymptomatic [4], but its association with recurrent intussusception remains unexplored to date. Furthermore, there have been no reported cases of untreated H. pylori infection deteriorating to the extent of causing HSP, which subsequently leads to intractable intussusception.…”
Section: Introductionmentioning
confidence: 99%
“…Household transmission, including oral-to-oral, fecal-oral, and gastrointestinal routes, is the primary mode. Approximately 90% of H. pylori infection cases are asymptomatic [4], but its association with recurrent intussusception remains unexplored to date. Furthermore, there have been no reported cases of untreated H. pylori infection deteriorating to the extent of causing HSP, which subsequently leads to intractable intussusception.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using gastric probiotics to treat gastric disease is of great clinical value in addressing H. pylori -induced gastritis in the future. Approximately 30% of children are infected with H. pylori , 22,23 and an increasing number of reports have shown that H. pylori infection affects pregnancy outcome; 24 however, the choice of antibiotics for children and pregnant women is limited. Additionally, in older adults, the use of antibiotics often leads to severe intestinal flora imbalance.…”
Section: Introductionmentioning
confidence: 99%